The cymothoid isopod Anilocra chromis is negatively associated with multiple metrics of host condition in the Caribbean damselfish Chromis multilineata - Jan-Alexis Barry; Kyle G. Jerris; Teresa R. Turner; Jenilee B. Robinson; Matthew D. Nicholson; Paul C. Sikkel (Marine Biology, 2026)
Parasitism is widespread among fishes in nature and can have significant impacts on individuals, populations, and communities. The family Cymothoidae includes over 380 species of parasitic isopods that infect a wide variety of host fishes, mostly in tropical and subtropical oceans. Despite their conspicuous nature, spatiotemporal patterns of infestation and effects on hosts have been studied for only a small percentage of species. The brown chromis ( Chromis multilineata ) is a common planktivorous damselfish associated with reefs in the tropical western Atlantic. Brown chromis are frequently infested with the large cymothoid isopod Anilocra chromis. In this study, we quantified the prevalence of infection among five sites and over two years in the US Virgin Islands (before and after major hurricanes). We further quantified the relationship between Anilocra infection status and the coinfection of other parasites as well as three metrics of potential impact: gonadal development, rate of food intake, and locomotion. Our results show that parasite prevalence differed significantly among sites. Additionally, while there was variation in coinfection with other parasites among sites, there was no relationship between the presence of Anilocra and the abundance of other parasites. There was a significant negative effect of Anilocra infection on male chromis gonads, feeding behavior (as determined by a decrease in bite-rates), and locomotion (as determined by an increase in fin-beats). Overall, these findings suggest that parasitism by Anilocra chromis is negatively associated with multiple metrics of fitness and health in host fishes, and thus likely has consequences at the population level.

Coral-dwelling Caribbean gobies exhibit distinct skin microbiota compared to other sympatric species - Ana Pereira; Raquel Xavier; Anya Brown; Jeanne Bloomberg; Gina C. Hendrick; Matthew D. Nicholson; Mallory Kastner; Marta C. Soares; Amy Apprill; Paul C. Sikkel (Coral Reefs, 2026)
Microbial communities fundamentally shape ecosystem function and biodiversity across all biological systems through complex dynamics. In coral reef ecosystems, understanding the dynamics of these microbial communities has become critical for predicting reef responses to environmental stressors. Fish skin microbiota are highly susceptible to environmental changes and may vary significantly across species and geographic locations, yet the extent to which these variations occur remain poorly understood. Here, we compared the skin microbiota of four closely related and sympatric cryptobenthic gobiid species, that exhibit different behavioral ecologies (cleaning vs.non-cleaning), ecological niches (water column, coral-, or sand-dwelling) and phylogenetic affinities ( Elacatinus vs. Coryphopterus ), yet reside in the same reef patches in St. Croix and Puerto Rico, eastern Caribbean. Coral-dwelling gobies, including cleaning sharknose and non-cleaning peppermint gobies, exhibited significantly lower microbial diversity compared to reef-hovering and sand-dwelling species (both non-cleaning). These coral dwellers showed unique microbial signatures despite having similar alpha diversity levels. Core microbiota analysis also revealed striking differences between coral-dwelling and reef-hovering/sand-dwelling species, with the core microbiome of the former dominated by Vibrio , Pseudoalteromonas , and Alteromonas in the case of cleaning gobies and by Endozoicomonas in the case of peppermint gobies, while reef-hovering and sand-dwelling gobies exhibited diverse core microbiota with greater overlap between species. Ecological niche occupancy and reef habitat selection appear to be primary drivers of skin microbiota composition in gobiid fishes, rather than cleaning behavior and/or host phylogenetic affinities alone, though species-specific skin mucus properties likely also contribute to selective bacterial colonization patterns.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Rudolf Nieuwenhuys (11 June 1927–4 November 2024): a scholarly life - Suzanne Bakker; Hans J. ten Donkelaar; Jan Voogd; Charles Nicholson; Lawrence H. Bannister; Loreta Medina; Ester Desfilis; Mario F. Wullimann; Johannes Meek; Luis Puelles; Cees A. J. Broere; Robert Turner; et al. (Brain Structure and Function, 2025)

Further reverberations of the 1983 impact with Saturn’s C ring - Richard G. French; Philip D. Nicholson; Matthew M. Hedman; Heikki Salo; Essam A. Marouf; Colleen A. McGhee-French; Nicole Rappaport; Joshua Colwell; Richard Jerousek; Victor M. Afigbo; Sophia Flury; Jolene Fong; et al. (Icarus, 2025)

Exploring policy coherence for land use transformations: The case of Scotland - Hebe Nicholson; Kirsty Blackstock; Jean Boucher; James Glendinning; Alexa Green; Alba Juarez-Bourke; Stan Martinat; Graciela Martínez Sánchez; Keith Matthews; Ian Merrell; Sam Poskitt; Steven Thomson (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Assessing how metal reef restoration structures shape the functional and taxonomic profile of coral-associated bacterial communities - Paige Strudwick; David J. Suggett; Justin R. Seymour; Matthew Z. DeMaere; Amanda Grima; John Edmondson; Alicia McArdle; Freda Nicholson; Emma F. Camp (Frontiers in Marine Science, 2024)
Significant threats to the long-term persistence of coral reefs have accelerated the adoption of coral propagation and out-planting approaches. However, how materials commonly used for propagation structures could potentially affect coral-associated bacterial communities remains untested. Here, we examined the impact of metal propagation structures on coral-associated bacterial communities. Fragments of the coral species Acropora millepora were grown on aluminium, sand/epoxy-coated steel (Reef Stars), and uncoated steel (rebar) structures. After 6 months, the functional and taxonomic profiles of coral-associated bacterial communities of propagated corals and reef colonies were characterised using amplicon (16S rRNA gene) and shotgun metagenomic sequencing. No differences in the phylogenetic structure or functional profile of coral-associated bacterial communities were observed between propagated corals and reef colonies. However, specific genes and pathways (e.g., lipid, nucleotide, and carbohydrate metabolism) were overrepresented in corals grown on different materials, and different taxa were indicative of the materials. These findings indicate that coral propagation on different materials may lead to differences in the individual bacterial taxa and functional potential of coral-associated bacterial communities, but how these contribute to changed holobiont fitness presents a key question to be addressed.

Functional diversity among coral reef fishes as consumers of ectoparasites - Matthew D. Nicholson; J. Andrés Pagán; Gina C. Hendrick; Paul C. Sikkel (Coral Reefs, 2024)

The Uranus system from occultation observations (1977–2006): Rings, pole direction, gravity field, and masses of Cressida, Cordelia, and Ophelia - Richard G. French; Matthew M. Hedman; Philip D. Nicholson; Pierre-Yves Longaretti; Colleen A. McGhee-French (Icarus, 2024)

Blood meal identification reveals extremely broad host range and host-bias in a temporary ectoparasite of coral reef fishes - Gina C. Hendrick; Matthew D. Nicholson; J. Andres Pagan; John M. Artim; Maureen C. Dolan; Paul C. Sikkel (Oecologia, 2023)

The complex shape of the outer edge of Saturn’s B ring, as observed in Cassini occultation data - Richard G. French; Philip D. Nicholson; Colleen A. McGhee-French; Pierre-Yves Longaretti; Matthew M. Hedman; Joshua Colwell; Essam A. Marouf; Nicole Rappaport; Sophia Flury; Jolene Fong; Ryan Maguire; Glen Steranka (Icarus, 2023)

First report of interspecific cleaning in a Pseudochromid, the dusky dottyback (Pseudochromis fuscus) - William E. Feeney; Rohan M. Brooker; Alexandra S. Grutter; Matthew D. Nicholson (Marine Biodiversity, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

The seven-lobed shape of the outer edge of Saturn’s A ring - Philip D. Nicholson; Richard G. French; Colleen A. McGhee-French; Pierre-Yves Longaretti; Matthew M. Hedman; Maryame El Moutamid; Joshua Colwell; Essam A. Marouf; Nicole Rappaport; Sophia Flury; Jolene Fong; Ryan Maguire; et al. (Icarus, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

South Africa’s private wildlife ranches protect globally significant populations of wild ungulates - W. Andrew Taylor; Matthew F. Child; Peter A. Lindsey; Samantha K. Nicholson; Claire Relton; Harriet T. Davies-Mostert (Biodiversity and Conservation, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

The effects of environment and ontogeny on the skin microbiome of two Stegastes damselfishes (Pomacentridae) from the eastern Caribbean Sea - Raquel Xavier; Ana Pereira; Andres Pagan; Gina C. Hendrick; Matthew D. Nicholson; Daniela Rosado; Marta C. Soares; Marcos Pérez-Losada; Paul C. Sikkel (Marine Biology, 2020)

Stable isotopes infer the value of Australia’s coastal vegetated ecosystems from fisheries - Holger Jänes; Peter I. Macreadie; Emily Nicholson; Daniel Ierodiaconou; Simon Reeves; Matthew D. Taylor; Paul E. Carnell (Fish and Fisheries, 2020)
Wild capture fisheries provide substantial input to the global economy through employment and revenue. The coastal zone is especially productive, accounting for just 7% of the total area of the ocean, but supporting an estimated 50% of the world's fisheries. Vegetated coastal ecosystems—seagrass meadows, tidal marshes and mangrove forests—are widely cited as providing nutritional input that underpin coastal fisheries production; however, quantitative evidence of this relationship is scarce. Using Australia as a case study, we synthesized fisheries stable isotope data to estimate nutritional input derived from coastal vegetated ecosystems and combined these “proportional contribution” estimates with total annual catch data from commercial fisheries to determine species‐specific dollar values for coastal vegetated ecosystems. Based on the data from 96 commercially important fish species across Australian states (total landings 14 × 10 6 tonnes pa), we provide a conservative estimate that Australia's coastal vegetated ecosystems contribute at least 78 million AUD per year to the fisheries economy. Two thirds of this contribution came from tidal marshes and seagrasses that were both equally valued at 31.5 million AUD per year (39.4%) followed by mangroves at 14.9 million AUD per year (18.6%). The highest dollar values of coastal ecosystems originated from eastern king prawn ( Melicertus plebejus ) and giant mud crab ( Scylla serrata ). This study demonstrates the substantial economic value supported by Australia's coastal vegetated ecosystems through commercial fisheries harvest. These estimates create further impetus to conserve and restore coastal wetlands and maintain their support of coastal fisheries into the future.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Ocean Time Series Observations of Changing Marine Ecosystems: An Era of Integration, Synthesis, and Societal Applications - Heather M. Benway; Laura Lorenzoni; Angelicque E. White; Björn Fiedler; Naomi M. Levine; David P. Nicholson; Michael D. DeGrandpre; Heidi M. Sosik; Matthew J. Church; Todd D. O’Brien; Margaret Leinen; Robert A. Weller; et al. (Frontiers in Marine Science, 2019)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

An Approach to Predict Risks to Wildlife Populations from Mercury and Other Stressors - Diane Nacci; Marguerite Pelletier; Jim Lake; Rick Bennett; John Nichols; Romona Haebler; Jason Grear; Anne Kuhn; Jane Copeland; Matthew Nicholson; Steven Walters; Wayne R. Munns (Ecotoxicology, 2005)